A chemogenetic platform for controlling plasma membrane signaling and synthetic signal oscillation. Issue 9 (15th September 2022) - Suzuki, Sachio; Nakamura, Akinobu; Hatano, Yuka; Yoshikawa, Masaru; Yoshii, Tatsuyuki; Sawada, Shunsuke; Atsuta-Tsunoda, Kyoko; Aoki, Kazuhiro; Tsukiji, Shinya
Summary: Chemogenetic methods enabling the rapid translocation of specific proteins to the plasma membrane (PM) in a single protein-single ligand manner are useful tools in cell biology. We recently developed a technique, in which proteins fused to an Escherichia coli dihydrofolate reductase (eDHFR) variant carrying N-terminal hexalysine residues are recruited from the cytoplasm to the PM using the synthetic myristoyl-d -Cys-tethered trimethoprim (m D cTMP) ligand. However, this system achieved PM-specific translocation only when the eDHFR tag was fused to the N terminus of proteins, thereby limiting its application. In this report, we engineered a universal PM-targeting tag for m D cTMP-induced protein translocation by grafting the hexalysine motif into an intra-loop region of eDHFR. We demonstrate the broad applicability of the new loop-engineered eDHFR tag and m D cTMP pair for conditional PM recruitment and activation of various tag-fused signaling proteins with different fusion configurations and for reversibly and repeatedly controlling protein localization to generate synthetic signal oscillations. Graphical abstract: Highlights: A single protein-single ligand method to control protein translocation was developed The loop-engineered protein tag can be fused or inserted at various protein sites Myristoyl-d -Cys-tethered ligand recruits tag-fused proteins to the plasma membrane This tagging system chemogenetically controls various signaling pathways Abstract : Suzuki et al. developed a chemogenetic method to facilitate synthetic molecule-mediated rapid recruitment of tag-fused proteins to the inner plasma membrane (PM). This method is easy to use and suitable for manipulating various signaling processes at the PM in a reversible and repeatable manner.